2023
DOI: 10.3390/coatings13030606
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Deterioration of Epoxy Coating on Carbon Steel by Pseudomonas aeruginosa

Abstract: Epoxy coating is a commonly used anticorrosive coating on metal surfaces. Pseudomonas aeruginosa has been reported to be able to accelerate the corrosion of metal materials, but its effect on the corrosion resistance of epoxy coatings is rarely reported. In this work, the accelerated deterioration of epoxy coating on carbon steel caused by marine Pseudomonas aeruginosa was investigated. The immersion tests of epoxy coatings in the sterile and P. aeruginosa-inoculated culture media with 100%, 10%, and 0% nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A similar approach was followed by Zhang et al [ 85 ], who analyzed the increasing hydrophilicity of epoxy coatings on steel specimen over time by measurement of the water contact angle They observed a reduction in the contact angle, from 70° to 63°, upon incubation of the coated samples with P. aeruginosa for 14 days. This decrease in contact angle suggests the formation of a biofilm on the surface, as reported by the authors.…”
Section: Analytical Methods For Characterization Of Bio-degraded Epoxymentioning
confidence: 98%
See 2 more Smart Citations
“…A similar approach was followed by Zhang et al [ 85 ], who analyzed the increasing hydrophilicity of epoxy coatings on steel specimen over time by measurement of the water contact angle They observed a reduction in the contact angle, from 70° to 63°, upon incubation of the coated samples with P. aeruginosa for 14 days. This decrease in contact angle suggests the formation of a biofilm on the surface, as reported by the authors.…”
Section: Analytical Methods For Characterization Of Bio-degraded Epoxymentioning
confidence: 98%
“…Zhang et al [ 85 ] applied EIS and measured the potentiodynamic polarization of epoxy coatings to evaluate their degradation by P. aeruginosa . They found that the presence of the bacteria promoted the degradation of the epoxy coating, especially under starvation conditions, and that the coating had lower low frequency impedance modulus and higher corrosion current density in the inoculated medium with starvation conditions.…”
Section: Analytical Methods For Characterization Of Bio-degraded Epoxymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, coating failure occurs due to an electrochemical reaction beneath the coating. In aggressive coastal marine environments, the causes of coating failures of offshore pipelines can be divided into the following two categories: corrosion due to microorganism activity [ 1 , 2 , 3 ] and maritime activities, including wet–dry cyclic conditions such as those at splash zone areas [ 4 ], and other/unknown causes [ 5 ]. In the aerospace industry, exterior coating failure occurs due to the high temperatures of engine exhausts and the drag effect of atmospheric friction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%